Common Error Pathways in CyberKnife™ Radiation Therapy - Mullins, Brandon T.; Mazur, Lukasz; Dance, Michael; McGurk, Ross; Schreiber, Eric; Marks, Lawrence B.; Shen, Colette J.; Lawrence, Michael V.; Chera, Bhishamjit S. (Frontiers in Oncology, 2020)
Purpose/Objectives Stereotactic radiosurgery (SRS) and stereotactic body radiation therapy (SBRT) may be considered “high risk” due to the high doses per fraction. We analyzed CyberKnife™ (CK) SRS and SBRT-related incidents that were prospectively reported to our in-house incident learning system (ILS) in order to identify severity, contributing factors, and common error pathways. Material and Methods From 2012 - 2019, 221 reported incidents related to the 4,569 CK fractions delivered (5.8%) were prospectively analyzed by our multi-professional Quality and Safety Committee with regard to severity, contributing factors, as well as the location where the incident occurred (tripped), where it was discovered (caught), and the safety barriers that were traversed (crossed) on the CK process map. Based on the particular step in the process map that incidents tripped, we categorized incidents into general error pathways. Results There were 205 severity grade 1-2 (did not reach patient or no clinical impact), 11 grade 3 (clinical impact unlikely), 5 grade 4 (altered the intended treatment), and 0 grade 5-6 (life-threatening or death) incidents, with human performance being the most common contributing factor (79% of incidents). Incidents most commonly tripped near the time when the practitioner requested CK simulation (e.g. pre-CK simulation fiducial marker placement) and most commonly caught during the physics pre-treatment checklist. The four general error pathways included pre-authorization, billing, and scheduling issues (n=119); plan quality (n=30); administration of IV contrast during simulation or pre-medications during treatment (n=22); and image guidance (n=12). Conclusion Most CK incidents led to little or no patient harm and most were related to billing and scheduling issues. Suboptimal human performance appeared to be the most common contributing factor to CK incidents. Additional study is warranted to develop and share best practices to reduce incidents to further improve patient safety.